Improving student learning outcomes through collaboration of the Student Teams Achievement Division (STAD) and Jigsaw learning models - Triansyah, Fadli Agus; Hasyim, Hasyim; Mutmainnah, Sri (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2022)
The problem in this study is the low student learning outcomes. This study aims to determine the increase in student learning outcomes using the collaborative learning model Student Teams Achievement Division (STAD) and Jigsaw in the Correspondence subject at SMK Negeri 1 Medan in the 2022/2023 academic year. This research uses using experimental method. This study's population was all class X AP students at SMK Negeri 1 Medan, totaling 144 people consisting of 4 classes. The sample in this study consisted of 2 courses, Class X AP-1 (Experimental), totaling 36 people, and X AP-2 (Control), totaling 36 people. The research instrument used to collect data was an objective test in the form of multiple choice, which destroyed 20 questions that had tested for validity with four answer choices. The data analysis showed that the experimental class's average value was 79.3, with a standard deviation of 8.38. At the same time, the average value of the Control class is 73.9, with a standard deviation of 7.94. Hypothesis testing was carried out using the t-test with dk = n1 + n2 – 2 at a significant level of 95%. From the calculation of the hypothesis obtained a tcount of 3.008 and ttable 1.6684. The results of hypothesis testing show that t count > t table (3.008 > 1.6684), then the hypothesis is accepted. From the results of this study, it can be concluded that there was an increase in student learning outcomes using the collaborative learning model Student Teams Achievement Division (STAD) and Jigsaw by 39.47% in the Class X AP Correspondence subject at SMK Negeri 1 Medan in the 2022/2023 academic year.